Multi-level Governance in rural development: Analysing experiences from LEADER for a Community-Led Local Development (CLLD) - Kim Pollermann; Petra Raue; Gitta Schnaut (European Regional Science Association (ERSA), 2014)
In the last funding periods there was steady increase in the number of LEADER-regions in Europe, and, at least in Germany, it is already evident that this gain will continue: for the 2014-2020 funding period there around 300 LAGs expected in comparison to 244 LAGs in the last period. For the new funding period new regulations envisages a Common Strategic Framework (CSF) to provide all EU Funds with a set of basic rules in line with the general principles - partnership, multi-level governance, equality and sustainability. Now there are common options for a so-called “Community-Led Local Development” (CLLD). Although LEADER is commonly called a bottom-up approach, it has to be pointed out that there is a high influence through a superordinated framework of funding regulations. So more precisely LEADER is neither "top-down" nor "bottom-up", but can classified as a “down up”-approach. This clarifies the basic understanding for the terms used in the context of multi-level governance. Second there is a look on the state of the art of LEADER-related research in the view of LEADER as a "down up" approach. Anyhow the experiences with LEADER in the last 25 years can give valuable insights. Altogether, the literature review already supports the need to have a multi-level-view on CLLD.
Keywords: R1; R5; R0; 330; Multi level Governance; LEADER; CLLD; rural development; Governance-Ansatz; Ländliche Entwicklung